Forest management guidelines to promote the conservation of Apennine brown bear in Italy - Rositi A (Forest@, 2019)
Forests provide a wide range of important ecosystem services and, among these benefits, biodiversity and wildlife habitat. Forest management (including no active control) deeply affects wildlife management, since it can alter habitat structure and productivity, speed-up evolution of ecosystems, and impact on wildlife ability to survive and reproduce. Unfortunately still very often, practitioners, forest planners and policy-makers fail to understand this opportunity. Forest management can maintain and enhance quality, quantity and availability of natural resources for wildlife, and therefore it is a valuable management tool long recognized in the wildlife practice. This is particularly true for species associated to forest ecosystems which are threatened or endangered, such as the Apennine brown bear (Ursus arctos marsicanus). Based on an extensive literature review on forest management-bear interactions, we report recommended management actions and associated working techniques, hereby illustrated and discussed in order to define a set of forest management guidelines meant to promote and encourage the adoption of adequate silviculture practices in Apennine forests, as well as to facilitate and support the range expansion of Apennine brown bear beyond its current core distribution. Our aim is also to present these guidelines to a wider scientific audience and decision-makers to foster their implementation into management practices, especially within protected areas. Finally, our ultimate goal is to fill the gap between disciplines such as silviculture and animal ecology, with the aim of stimulating the multidisciplinary approach requested not only for the conservation of the Apennine brown bear but for the integrated and enhanced management of wildlife in general.